Recent advances in the asymmetric reduction of imines by recycled catalyst systems. Issue 3 (23rd December 2021) - Deng, Lidan; Liu, Xingwang; Song, Shihua
Abstract : Recent advances relating to the asymmetric reduction of imines to afford optically active amines via recyclable catalyst systems are reviewed. Abstract : Chiral amines are widely found in nature, and many of them possess significant biological and synthetic value. The catalytic asymmetric syntheses of optically active amines have gained enormous interest. Currently, fruitful and prime strategies for obtaining them rely on homogeneous catalysts. Due to the pressure to develop highly economical and environmentally friendly homogeneous catalysis, it is highly desirable to develop recyclable catalyst systems for the reduction of imines to deliver chiral amines with outstanding enantioselectivity, not only reusing expensive catalysts but also simplifying the work-up procedures. This review summarizes recent advances in this field, which are classified into two typical areas: (1) heterogeneous asymmetric catalysis via the direct immobilization of active catalysts; and (2) homogeneous asymmetric catalysis via novel catalysts and elaborate work-ups. For the selected examples, we focused on the design, synthesis, and recovery of active catalysts, and on representative outcomes and critical reviews.